2018
DOI: 10.1016/j.bbadis.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic markers of fatigue: Association between circulating metabolome and fatigue in women with chronic widespread pain

Abstract: BackgroundFatigue is a sensation of unbearable tiredness that frequently accompanies chronic widespread musculoskeletal pain (CWP) and inflammatory joint disease. Its mechanisms are poorly understood and there is a lack of effective biomarkers for diagnosis and onset prediction. We studied the circulating metabolome in a population sample characterised for CWP to identify biomarkers showing specificity for fatigue.Material and methodsUntargeted metabolomic profiling was conducted on fasting plasma and serum sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Our previous studies suggested involvement of neurological pathways in aetiology of CWP, 14 and showed that its appearance significantly correlates with neuropathic pain features, 20 and with fatigue and depression. 3 , 9 This study further suggests that steroid pathways are involved in the mechanism of interaction between frailty and pain.…”
Section: Discussionsupporting
confidence: 51%
“…Our previous studies suggested involvement of neurological pathways in aetiology of CWP, 14 and showed that its appearance significantly correlates with neuropathic pain features, 20 and with fatigue and depression. 3 , 9 This study further suggests that steroid pathways are involved in the mechanism of interaction between frailty and pain.…”
Section: Discussionsupporting
confidence: 51%
“…4B). We could not discriminate between these two metabolites as they are structurally similar and have the same molecular mass and fragmentation pattern in LC-MS. We also analysed the metabolites described in the literature, such as creatinine [31,55], platelet activating factor [11] and acetylcarnitine [25]. To infer alterations in the biological processes and metabolic and functional pathways associated with the differentially expressed metabolites, we used MetScape [44] and Ingenuity Pathway Analysis® (QIAGEN) (IPA).…”
Section: Resultsmentioning
confidence: 99%
“…Investigations of the metabolome (16)(17)(18)(19)(20) and (gut) microbiome (21)(22)(23)(24)(25) in CFS, both aspects that are inadvertently linked with in ammation (16,26), showed interesting, albeit inconsistent, results (23,25). Up until this moment, no such studies were conducted in QFS.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing CFS patients to HC, studies on metabolomic pro les consistently found differences between these groups (17)(18)(19)(20). Armstrong et al found that CFS patients show lower levels of glutamine and ornithine compared to HC (20).…”
Section: Discussionmentioning
confidence: 99%